"NIMBY" or Citizen Participation? - Clary, Bruce (Maine Policy Review, 1997)
Bruce Clary has written on citizen participation and its role in democratic societies for more than two decades. In the Margaret Chase Smith Essay, he writes about the NIMBY (“Not in My Backyard”) phenomenon and his own experiences as a citizen participant in land-use siting issues in Maine and elsewhere.
Keywords: civic engagement